Implementasi dan Hambatan Dalam Penerapan Kurikulum Merdeka di Sekolah Dasar: Studi Kepustakaan - Mooy, Angela Paulin; Nawangsari, Nur Ainy Fardana (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the implementation of the independent curriculum in elementary schools and the obstacles to implementing the independent curriculum in elementary schools. The research method used is a literature review with qualitative methods. The secondary data sources used came from 16 national journal articles. The research results show that the implementation of the independent curriculum in elementary schools can be seen from five aspects of the independent curriculum, namely, 1) development of the school operational curriculum; 2) use of teaching tools; 3) Pancasila profile project; 4) learning according to the student's learning achievement stage; 5) innovative development. The obstacles in implementing the independent curriculum in elementary schools are, 1) related to infrastructure; 2) teaching staff and teachers; 3) conditions of students, environment, and family; 4) inequality in government policies.